2013
DOI: 10.1177/0164027513510324
|View full text |Cite
|
Sign up to set email alerts
|

A Research Note on the Relationship Between Long Working Hours and Weight Gain for Older Workers in the United States

Abstract: Working long hours may be related to obesity in older adults. No studies have focused on older workers and long work hours, although the risk of obesity is high among this population group. This study is the first attempt to investigate the relationship between obesity and the older workforce. Panel data from the Health and Retirement Study are examined using Cox regression techniques. We found that older workers who work more than 59 hr a week are more likely to gain weight than older workers who work less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
2
17
0
1
Order By: Relevance
“…66 Similar results were noted for older workers based on panel data from the Health and Retirement Study. 72 Here, older employees who worked more than 59 hours per week were 23% more likely to gain weight as compared to those who worked less than 59 hours per week. Hauck and Hollingsworth reported that employment itself is associated with more weight gain and less weight loss among middle-aged women.…”
Section: Impact Of the Workplace On Obesitymentioning
confidence: 84%
“…66 Similar results were noted for older workers based on panel data from the Health and Retirement Study. 72 Here, older employees who worked more than 59 hours per week were 23% more likely to gain weight as compared to those who worked less than 59 hours per week. Hauck and Hollingsworth reported that employment itself is associated with more weight gain and less weight loss among middle-aged women.…”
Section: Impact Of the Workplace On Obesitymentioning
confidence: 84%
“…For example, in an OECD context, Turkey has one of highest proportions of workers who work long hours in the workforce. It is well established that working long hours has many negative side effects including obesity (Mercan 2014). Therefore, researchers need to investigate the effects of obesity both on workers' health and on extending working life.…”
Section: Assessment and Conclusionmentioning
confidence: 99%
“…Furthermore, longer work hours are related to weight gain (Au & Hollingsworth, 2011;Mercan, 2014) and higher body mass index (DiMilla, 2009). It is also associated with unhealthy behaviors; for example smoking, consumption of alcohol and coffee, having unbalanced diets and inadequate leisure time physical activity.…”
Section: Obesity and Occupationmentioning
confidence: 99%
“…Nevertheless, most of the studies focus on the prevalence of obesity within occupations and to some extent related health behaviors. Even though there are several studies, which investigate the relationship between obesity and working hours (Au, Hauck, & Hollingsworth, 2013;Mercan, 2014), there is no previous study investigating the effect of working hours on obesity by occupation groups. This study is first to examine the probability of being obese in 40 occupational groups focusing on the effect of working hours.…”
mentioning
confidence: 99%